Treatment of Behçet's Disease: An Algorithmic Multidisciplinary Approach - Alpsoy, Erkan; Leccese, Pietro; Emmi, Giacomo; Ohno, Shigeaki (Frontiers in Medicine, 2021)
Behçet's disease (BD) is a chronic, relapsing inflammatory, multisystem disease of unknown aetiology. The disease has a wide clinical spectrum of mucocutaneous lesions and ocular, vascular, articular, neurologic, gastrointestinal and cardiac involvement. Although the number of effective drugs used in the disease's treatment has increased in recent years, BD is still associated with severe morbidity because of mainly mucocutaneous, articular and ocular symptoms and an increased mortality because of large vessel, neurological, gastrointestinal and cardiac involvement. Many factors are associated with a more serious course, such as male gender and a younger age of onset. While the severity of the disease is more pronounced in the first years of the disease, it decreases in most patients after the age of forties. The primary goal of treatment should be the prevention of irreversible organ damage. Therefore, early diagnosis and appropriate treatment and close follow-up are mandatory to reduce the morbidity and mortality of the disease. Treatment varies depending on the organ involved and the severity of the involvement. For all these reasons, the treatment should be personalized and arranged with a multidisciplinary approach according to the organs involved. Treatment is mainly based on suppression of the inflammatory attacks of the disease using local and systemic immunomodulatory and immunosuppressive drugs. In this review, based on the mainly controlled studies and personal experience in clinical practice and basic research in this field, we propose a stepwise, symptom-based, algorithmic approach for the management of BD with a holistic perspective.